Dollar-Cost Average plan in EMU countries: could it be beneficial? What the data say. - Vasileiou, Evangelos; Apostolidis, Dimitrios (International Conference on Business and Economics - Hellenic Open University, 2023)
This study examines a real case scenario using real data under the assumption of a long-term investment horizon. We examine the Dollar Cost Average, Cost Average Plan (CAP) in our case, and attempt to ascertain whether it could prove beneficial for an investor that does not have a significant amount of money to invest when the plan begins. We compare the outcome of the CAP with the alternative scenario of investing a monthly amount in a deposits account, which is in real terms the most comparable plan to the CAP. Using data from January, 2003 to November, 2021 from a wide range of ten (10) European Monetary Union countries, we compare the empirical evidence of these results and we reach the conclusions that CAP outperforms the seasonal bank deposits plan. Moreover, we compare these strategies with the Buy-and-Hold (BnH) strategy, as most studies do, and we conclude that CAP is more beneficial for highly volatile and less uptrend markets than a BnH strategy. Jel Classifications: G1; G11; N2 Keywords: Dollar Cost Averaging; Investment Strategies; Investment Decisions; Investment Plans.